2014
DOI: 10.17503/agrivita-2014-36-3-268-277
|View full text |Cite
|
Sign up to set email alerts
|

DROUGHT TOLERANCE OF LOCAL ROTE AND CHECK VARIETIES OF GROUNDNUT (Arachis hypogaea L.) UNDER DRY SEASON IN TWO LOCATIONS IN EAST NUSA TENGGARA

Abstract: Groundnut is the most important pulse crop in East Nusa Tenggara (ENT); however, the crop yield in ENT is low due to erratic climatic condition, drought stress, and low yielding ability of most cultivated genotypes. Local Rote is a well-known local groundnut variety in ENT, which is a potential superior variety and parental source due its large seed size and high yielding ability. Information on its resistance to abiotic and biotic stresses is important for its future development. Five groundnut genotypes, Loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…Mean tuber yields (kg ha -1 ) under both conditions were used to determine the drought tolerance level of tested sweet potato genotypes based on the calculated drought tolerance indices previously employed by various studies. The indices included MP (mean performance), STI (stress tolerance index), and SSI (stress susceptibility index) (Bidinger et al 1978;Fischer and Maurer 1978;Mau et al , 2014, GMP (geometric mean performance), MRP (mean relative performance), HARM (harmonic yield), YSI (yield stress index), REI (relative expression index), and SNPI= Stress non-stress production index (Farshadfar and Sutka 2002;Moosavi et al 2008;Farshadfar and Elyasi 2012;Ali et al 2013;Mau et al 2019).…”
Section: Observation and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Mean tuber yields (kg ha -1 ) under both conditions were used to determine the drought tolerance level of tested sweet potato genotypes based on the calculated drought tolerance indices previously employed by various studies. The indices included MP (mean performance), STI (stress tolerance index), and SSI (stress susceptibility index) (Bidinger et al 1978;Fischer and Maurer 1978;Mau et al , 2014, GMP (geometric mean performance), MRP (mean relative performance), HARM (harmonic yield), YSI (yield stress index), REI (relative expression index), and SNPI= Stress non-stress production index (Farshadfar and Sutka 2002;Moosavi et al 2008;Farshadfar and Elyasi 2012;Ali et al 2013;Mau et al 2019).…”
Section: Observation and Data Analysismentioning
confidence: 99%
“…Most of the drought tolerance indices used to select the above drought tolerant sweet potato genotypes have been shown to be effective in selecting drought-tolerant genotypes of various crops (Fischer and Maurer 1978;Bidinger et al 1978;Farshadfar and Sutka 2002;Moosavi et al 2008;Ali et al 2013;Mau et al 2014;Mau et al 2019). The six selected sweet potato genotypes also exhibited high yielding performance (≥ 20 t ha -1 tuber yield) under no stress condition and moderate yielding performance (≥ 10 t ha -1 ) under water-stressed condition.…”
Section: Selected Genotypesmentioning
confidence: 99%
“…In summary, to date, more than 20 indices have been employed for selection of drought-tolerant varieties, with varying degree of effectiveness depending on the particular crop species. Among these, STI, SSI, MP, MRP, HARM, REI, ATI, GMP, MSTIK1, MSTIK2, SNPI, SSPI, YI, RDI, and RDY have previously been reported to be the most suitable indices for various crops (Naghavi et al, 2003;Sio-Se et al, 2006;Moosavi et al, 2008;Bahar and Yildirim, 2010;Golbashy et al, 2010;Dadbakhsh et al, 2011;Farshadfar and Elyasi, 2012;Mau et al, 2014;Ali and El-Sadek, 2016;Bennani et al, 2017) but these have not been assessed in upland rice. Thus, the purposes of the study reported in this paper were (1) to assess the effectiveness of drought tolerance indices for selection of drought tolerance in upland rice, and (2) to determine the most suitable index for identifying drought tolerant, high-yielding upland rice genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…e return period prediction allows farmers to formulate adaptation strategies for drought events to minimize losses due to crop failure. Mau et al [31] studied ground nut productivity in NTT and found that unpredictable environ-mental conditions, especially the uncertain rainfalls, and water shortage have been the major limiting factors for groundnut production in this region. Unavailability of high yielding and well adapted varieties are additional limiting factors that cause yield of this crop in this region very low.…”
Section: Discussionmentioning
confidence: 99%
“…is study uses daily rainfall data measured in millimetres per day for the period from 1 January 2005 to 31 December 2017 recorded at the following nine stations: Komodo, Frans Sales Lega, Fransiskus Xaverius, Gewayantana, Mali, Umbu Mehang Kunda, Kupang, Eltari, and Tardamu. e data were obtained from the official website of the Agency for Meteorology, Climatology and Geophysics (BMKG), which is available at http://dataonline.bmkg.go.id.…”
Section: Datamentioning
confidence: 99%